The Lisbon and Seville stations: their place within railway station typology and their impact on the organization of urban space - Matos, Ana Cardoso de (2020)
The introduction of railway transportation to the Iberian Peninsula entailed the construction of a series of structures which were essential to its functioning, from the railway lines themselves to water deposits, workshops, and stations. The latter assumed varying degrees of importance, depending on their location along the lines: those which were located in cities, being the starting points of railway lines, were bigger-sized and more important. While some stations were little more than mere halts, very simply built, their urban counterparts in the big cities constituted great public works and are considered, as a group, to be among the most characteristic examples of industrial architecture. In the 19th century, railway stations were the most visible picture of the novel architectonic programmes using cutting-edge technology, regarding materials – iron, steel, and glass – and also lighting, through the use of electricity. This turned them into privileged spaces for applying and demonstrating materials, styles, techniques, functions, and meanings that crucially altered the ‘street aesthetics’, leading to a profound renewal of both the morphological organization of cities and the urban landscape. In this article, we aim to make a comparative study between two stations in Lisbon (Rossio and Santa Apolónia) and another two in Seville (La Plaza de Armas and San Bernardo) to investigate, on the one hand, how they fit into the typology of their respective countries’ railway stations, and on the other, whether they had identical influence on the organization and enlargement of their cities’ urban spaces.